Long-Term Liraglutide Administration Induces Pancreas Neogenesis in Adult T2DM Mice. (23rd June 2020) - Deng, Hongjun; Yang, Fengying; Ma, Xiaoyi; Wang, Ying; Chen, Qi; Yuan, Li
In vivo beta-cell neogenesis may be one way to treat diabetes. We aimed to investigate the effect of glucagon-like peptide-1 (GLP-1) on beta-cell neogenesis in type 2 diabetes mellitus (T2DM). Male C57BL/6J mice, 6 wk old, were randomly divided into three groups: Control, T2DM, and T2DM + Lira. T2DM was induced using high-fat diet and intraperitoneal injection of streptozotocin (40 mg/kg/d for 3 d). At 8 wk after streptozotocin injection, T2DM + Lira group was injected intraperitoneally with GLP-1 analog liraglutide (0.8 mg/kg/d) for 4 wk. Apparently for the first time, we report the appearance of a primitive bud connected to pancreas in all adult mice from each group. The primitive bud was characterized by scattered single monohormonal cells expressing insulin, GLP-1, somatostatin, or pancreatic polypeptide, and four-hormonal cells, but no acinar cells and ductal epithelial cells. Monohormonal cells in it were small, newborn, immature cells that rapidly proliferated and expressed cell markers indicative of immaturity. In parallel, Ngn3 + endocrine progenitors and Nestin + cells existed in the primitive bud. Liraglutide facilitated neogenesis and rapid growth of acinar cells, pancreatic ducts, and blood vessels in the primitive bud. Meanwhile, scattered hormonal cells aggregated into cell clusters and grew into larger islets; polyhormonal cells differentiated into monohormonal cells. Extensive growth of exocrine and endocrine glands resulted in the neogenesis of immature pancreatic lobes in adult mice of T2DM + Lira group. Contrary to predominant acinar cells in mature pancreatic lobes, there were still a substantial number of mesenchymal cells around acinar cells in immature pancreatic lobes, which resulted in the loose appearance. Our results suggest that adult mice preserve the capacity of pancreatic neogenesis from the primitive bud, which liraglutide facilitates in adult T2DM mice. To our knowledge, this is the first time such a phenomenon has been reported.